Visual Outcomes and Patient Satisfaction of Two Continuous Range of Vision Intraocular Lenses - Micheletti JM; Hall B; Smiley HG; Langston WJ (Clinical Ophthalmology)
J Morgan Micheletti,1 Brad Hall,2 Hayden G Smiley,3 William J Langston4 1Berkeley Eye Center, Houston, TX, USA; 2Sengi, Penniac, NB, Canada; 3Baylor Scott and White Medical Center, Temple, TX, USA; 4Long School of Medicine, San Antonio, TX, USACorrespondence: J Morgan Micheletti, Berkeley Eye Center, Houston, TX, USA, Tel +1-713-526-1600, Email morgan.micheletti@gmail.comPurpose: To determine if visual outcomes with PanOptix are non-inferior to visual outcomes with Synergy.Methods: This was an ambispective, single center, comparative, bilateral, observational study. Patients received bilateral implantation with either PanOptix or Synergy intraocular lenses (IOLs) and were enrolled at least 5 months after surgeries. Patients with postoperative spherical equivalent ± 0.50D and astigmatism ≤ 0.75D in both eyes were enrolled. Postoperatively, patients were tested for binocular uncorrected and distance corrected visual acuities at distance, intermediate (60cm), and near (40cm and 33cm), binocular defocus curve, and were administered questionnaires about quality of vision (QUVID) and spectacle independence (IOLSAT).Results: A total of 230 subjects completed the study, 153 in the PanOptix group and 77 in the Synergy group. Non-inferiority of visual acuities were confirmed for all testing distances, with and without distance correction in place. No significant differences were observed for the binocular defocus curves (p > 0.05). Severity of starburst, halo, and glare were rated as “None” in 65% (98/150), 38% (58/152), and 48% (72/151) of subjects with the PanOptix Group, compared to 49% (37/76), 38% (29/77), and 55% (42/77) for the Synergy Group, respectively. The percentage of patients “Satisfied” or “Very Satisfied” with their vision was 89% (136/153) in the PanOptix group and 94% (72/77) in the Synergy group.Conclusion: The results of this study suggest excellent visual acuities at distance, intermediate, and near, high spectacle independence, and high patient satisfaction with both the PanOptix and Synergy IOLs. The incidence of starbursts and blurred vision, as well as visual acuities at extreme near (33 cm), may be higher with the Synergy IOL.Keywords: panoptix, synergy, cataract surgery, continuous range of vision